Diseño de Manejo Integrado de Plagas para el control de arañita marrón (Oligonychus punicae Hirst) en Persea americana Mill. en Chao - La Libertad en el 2012 - Gutiérrez Marín, Vanessa Lizbeth (2012)
The present work realized in the zone of Chao, in Chao district, Viru province, department of La Libertad to design the integrated pest management to control brown spider (Oligonychus punicae Hirst) of Persea americana Mill in 2012. To identify the phases in the development of a program of integrated pest open interview was conducted at farmer Jimmy Criollo Edson Llanos, and evaluated the experiences gained in the management of their culture through a survey that had the technical support to designing integrated in the control of brown mite Oligonychus punicae Hirst. appropriate for your area. From this information, we established the evaluation phytosanitary methodology, reference thresholds for phytosanitary management and control strategies to brown spider Oligonychus punicae Hirst. depending phenological stages on the cultivation of avocado.